The influence of parent–child relationships on the learning adaptability of left-behind children: the mediating role of peer attachment and the moderating role of separation duration - Chen, Ning; Zhao, Keyun; Chen, I-Hua; Liu, Guanling (Frontiers in Psychology, 2023)
Studies have revealed the influence of parent-child relationships on the learning adaptability of left-behind children. However, the researchers have not explored the mechanisms underlying the parent-child relationships of left-behind children. The purpose of this study was not only to examine the mediating role of peer attachment in the relationship between parent-child relationships and learning adaptability but also to explore the moderating variable of separation duration in the relationship between parent-child relationships and peer attachment. The study examined 1555 left-behind children and found that, after controlling for gender and grade, parent-child relationships positively predicted learning adaptability; peer attachment mediated the relationship between parent-child relationships and learning adaptability, and separation duration moderated the effect of parent-child relationships on peer attachment. The study reveals the importance of parent-child relationships and peer attachment in the growth and development of left-behind children, which is important for the improvement of left-behind children’s learning adaptability.